Представники родини Rosaceae Juss. для оптимізації садово-паркових ландшафтів Полісся та Лісостепу України - Trofimenko, N.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
Ornamental characteristics of plants belonging to Rosaceae Juss. family and forms of separate genera of this family are described. Their habitats are cited. These plans are recommended as the best for landscape optimization in Polissia and Forest Steppe of Ukraine.